A Review of Resourcing Approaches in Post Disaster Housing Reconstruction - Enshassi, Adnan Ali; Saleh, Nour; Sundermeier, Matthias (International Journal of Sustainable Construction Engineering and Technology, 2020)
In recent years, the occurrence of disasters is on increase and causes heavy human losses and massive destruction especially on housing sector. Post disaster housing reconstruction (PDHR) is a part of the cycle of four disaster management stages: mitigation, preparedness, response; and recovery and reconstruction. Availability of resources is a key factor to a successful PDHR project. This study systematically reviews 94 articles during the period of 2003 and 2019 on different experiences of PDHR. The study reports the various resourcing approaches of PDHR, their strategies, and their advantages and disadvantages. It identifies the critical success factors that led to a successful resourcing approach. The most cited factors reported in this study can be used as a guide to reconstruction practitioner to choose the most appropriate resourcing approach to reconstruct houses after disasters.